Sweet potato (Ipomoea batatas L. Lam.) cultivation and potentialities - Vendrame, Larissa Pereira de Castro (2023)
Sweet potato is an American origin root with a growing demand, for both human and animal feed, in this case including the aerial part. The production of sweet potato is stable worldwide. For Brazil, the acreage, volume, and consumption have arisen since 2012. In this specific case, the increase is explained by claimed health benefits and the broad production of value-added derivative products. The purpose of this chapter is to review the importance of sweet potato as a crop, and its market potential in South America. The addressed topics are production and trade, consumption, chemical composition of the main cultivars, current cultivation practices, derivative food products, and processing. Based on these facts, improvements are recommended regarding the food usage of this species, development of new cultivars and cultural practices, to address different demands of this productive chain. Thus, these demands will require efforts from breeders, food technologists, agricultural economists, and industries.